2012
DOI: 10.1501/egifak_0000001239
|View full text |Cite
|
Sign up to set email alerts
|

Social-emotional problems observed in gifted children

Abstract: ABSTRACT. The goal of this paper is to increase awareness related to social-emotional problems experienced by gifted children lacking support systems suited to their needs and to describe solutions to minimize associated risks. The concept of "gifted" is defined and reasons for differences in social-emotional needs of gifted children together with how asynchronous development can be an important factor effecting their social-emotional states are explained. Different problems in this context are then considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Accordingly, it is seen that the number of studies on disadvantaged individuals (Bumpus, 2014;Eminağaoğlu, 2006;Er, 2009;Kidd & Shahar, 2008) is higher than studies conducted with gifted individuals (Chen vd., 2017;King, 2009;Kline & Short, 1991). In our country, the variables of self-esteem (Albayrak-Dengiz, 2014;Altun & Yazıcı, 2012;Büyüktaşkapu-Soydan & Kabar, 2020;Olgun-Kaval, 2014), parental attitudes (Afat, 2013), peer relations (Erol, 2015;Oğurlu, 2010;Özbey et al, 2020), emotional intelligence (Koçak & İçmenoğlu, 2012), communication skills (Koç, 2015), and social emotional problems (Saranlı & Metin, 2012) of gifted students were examined in researchs. However, in Turkey, there is one research (Uçak-Azboy, 2020) on the resilience of gifted children.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Accordingly, it is seen that the number of studies on disadvantaged individuals (Bumpus, 2014;Eminağaoğlu, 2006;Er, 2009;Kidd & Shahar, 2008) is higher than studies conducted with gifted individuals (Chen vd., 2017;King, 2009;Kline & Short, 1991). In our country, the variables of self-esteem (Albayrak-Dengiz, 2014;Altun & Yazıcı, 2012;Büyüktaşkapu-Soydan & Kabar, 2020;Olgun-Kaval, 2014), parental attitudes (Afat, 2013), peer relations (Erol, 2015;Oğurlu, 2010;Özbey et al, 2020), emotional intelligence (Koçak & İçmenoğlu, 2012), communication skills (Koç, 2015), and social emotional problems (Saranlı & Metin, 2012) of gifted students were examined in researchs. However, in Turkey, there is one research (Uçak-Azboy, 2020) on the resilience of gifted children.…”
Section: Introductionmentioning
confidence: 92%
“…Chen vd., 2017;King, 2009;Kline & Short, 1991) oranla daha fazla olduğu görülmektedir. Ülkemizde ise, özel yetenekli öğrencilerde benlik saygısı (Albayrak-Dengiz, 2014;Altun & Yazıcı, 2012;Büyüktaşkapu-Soydan & Kabar, 2020;Olgun-Kaval, 2014), ebeveyn tutumları (Afat, 2013), akran ilişkileri (Erol, 2015;Oğurlu, 2010;Özbey vd., 2021), duygusal zeka (Koçak & İçmenoğlu, 2012), iletişim becerileri (Koç, 2015), sosyal duygusal sorunlar (Saranlı & Metin, 2012) değişkenleri araştırmalarda ele alınmış olsa da, özel yetenekli öğrencilerin psikolojik sağlamlığına yönelik yapılmış bir araştırmaya rastlanmış (Uçak-Azboy, 2020), bir araştırmada da özel yetenekli bireylerin ailelerinde psikolojik sağlamlığın incelendiği görülmüştür (Kahvecioğlu, 2016).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…However, it is seen that only a limited number of studies to determine the psychological needs of gifted children has been conducted in our country. In these studies, it was noted that social skills (Elcik & Bayındır, 2015), perfectionism (Toplu, 2013), self-perceptions (Altun &Yazıcı, 2012;Tokmak, 2016), psychological counseling needs (Doğan & Kesici, 2015;Sürücü, 2013) and behavioral problems (Gür, 2011;Saranlı &Metin, 2012) of gifted children were among the issues investigated. When literature was reviewed, although there were some studies on the selfperceptions and social behaviors of children with normal development, no research was found that addressed the self-perceptions and social behaviors of gifted children in Turkey (Cerrahoğlu & Balcı-Çiçek, 2017;Tazeoğlu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They feel a need for a more challenging education, an introduction to different subjects, problem solving and creative thinking skills, and unique approaches to solutions for problems. Gifted students need to ruminate on their ideas, discuss them, think using possibilities, abstractions, and metaphorical strategies; to generalize and test them [8]. Gifted students who do not receive an education based around their characteristics and needs tend to achieve below their potentials, and once their sense of competence has weakened, which is to say when they are unable to realize their purpose in life, considering how a large portion of contribution to society comes from these people, it's apparent that overlooking this group can lead to a negative outcome [9].…”
Section: Introductionmentioning
confidence: 99%